Genome-wide characterization of TNF receptor-associated factors in the Chinese soft-shelled turtle Pelodiscus sinensis and their expression profiling in response to Aeromonas hydrophila challenge. Issue 101 (June 2020) - Liu, Tengfei; Wu, Yongjie; Han, Yawen; Liu, Qingyang; Chen, Shulin; Zhao, Huiying
Abstract: Tumor necrosis factor receptor (TNFR)-associated factors (TRAFs) are a family of crucial signaling molecules that mediate the signal transduction of various immune signaling pathways. Extensive studies have demonstrated that TRAFs play vital roles in regulating cellular immune responses. However, the biological functions and expression profiling of TRAFs in Chinese soft-shelled turtle ( Pelodiscus sinensis ) remain unclear. In this study, the genes of the PsTRAF family at the genome-wide level were identified in P. sinensis, revealing six PsTRAF members that contained the conserved TRAF domain in the C-terminal regions. Molecular evolutionary analysis showed that PsTRAFs shared close evolutionary relationships and similar protein crystal structures with the TRAF homologs from other turtles, indicating the evolutionary conservation of PsTRAFs . Further expression analysis revealed the tissue-specific expression of PsTRAF genes. Obvious variations in the expression of PsTRAF genes were observed in the spleen in response to Aeromonas hydrophila infection. Three PsTRAF genes, PsTRAF2, PsTRAF3, and PsTRAF6, were significantly upregulated at the mRNA and protein levels post-infection, indicating their potential function in the immune response. Moreover, the protein-protein associations of PsTRAFs with several signaling receptors were predicted in P. sinensis . These results provide a basis for the investigation of the functional roles of PsTRAFs in immune defense against bacterial infection. Highlights: Six PsTRAF genes contained the conserved TRAF domain are identified. PsTRAF genes show evolutionary conservation among different turtle species. Variations of PsTRAF gene expressions respond to Aeromonas hydrophila infection. Protein expression levels of critical PsTRAFs increased after bacterial infection. PsTRAFs putatively participate in the immune defense against bacterial infection.